'Craft for social good': do on the job training of artisans' impact on their vulnerability to poverty? Evidence from Kibera. Issue 1 (2nd January 2022) - Wang Sonne, Soazic Elise; Kinoti, Timothy
ABSTRACT: In this paper, We study how an on the job training program targeting low-income jewellery artisans (SOKO) impact on their vulnerability to poverty in Kenya. We use propensity score matching to assess SOKO's impact on the poverty likelihood of artisans. We find that SOKO artisans have a lower vulnerability to poverty as compared to artisans with similar socio-demographic characteristics but no SOKO affiliation. We also find that female artisans affiliated with SOKO are more vulnerable to poverty as compared to male artisans. Our findings are robust to various propensity score matching specifications and to alternative measures of vulnerability to poverty.